2019
DOI: 10.1002/cncr.32342
|View full text |Cite
|
Sign up to set email alerts
|

A contemporary analysis of racial disparities in recommended and received treatment for head and neck cancer

Abstract: BACKGROUND: Racial disparities in squamous cell carcinoma of the head and neck (HNSCC) negatively affect non-Hispanic black (NHB) patients. This study was aimed at understanding how treatment is prescribed and received across all HNSCC subsites. METHODS: With the National Cancer Database, patients from 2004 to 2014 with surgically resectable HNSCCs, including tumors of the oral cavity (OC), oropharynx (OP), hypopharynx (HP), and larynx (LX), were studied. The treatment received was either upfront surgery or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 43 publications
3
32
0
Order By: Relevance
“…Our results are consistent with the literature that Black patients present with more advanced disease 12 and are less likely to receive treatment. 28,29 Black patients historically have higher rates of not receiving definitive cancer treatment, such as surgery, radiotherapy, or a combination of the two, which our study also shows. 30 Interestingly, we found that Black patients also experienced higher rates of escalation of treatment (surgery and chemoradiotherapy).…”
Section: Discussionsupporting
confidence: 69%
“…Our results are consistent with the literature that Black patients present with more advanced disease 12 and are less likely to receive treatment. 28,29 Black patients historically have higher rates of not receiving definitive cancer treatment, such as surgery, radiotherapy, or a combination of the two, which our study also shows. 30 Interestingly, we found that Black patients also experienced higher rates of escalation of treatment (surgery and chemoradiotherapy).…”
Section: Discussionsupporting
confidence: 69%
“…Our study is consistent with several others that have noted disparities in the receipt of guideline-concordant cancer care and overall outcomes among Black patients due to a number of patient-and provider-driven factors. [16][17][18][19][20][21][22][23] In addition, our study is consistent with several others that have revealed undertreatment of female patients compared with their male counterparts with respect to other disease sites and modalities of cancer care. 24 We have previously shown that older populations are less likely to receive perioperative RT 11 due to a number of potential factors that others have investigated, including physician-based factors such as hesitancy to recommend more-intensive treatment due to preconceived biases regarding patient frailty, and patient-related factors such as prioritization of immediate convenience and quality of life over long-term outcomes and survival.…”
Section: Discussionsupporting
confidence: 91%
“…For example, a recent study showed that black patients were at a 10% greater risk of mortality within 90 days after treatment of HNSCC 20 . Black patients were also 13% less likely to undergo the standard surgery for oral cavity squamous cell carcinoma and more likely to refuse a recommended surgery across all HNSCC subsites 5,21 . These results suggest important differences in care and the patient‐physician relationship between black and white patients.…”
Section: Discussionmentioning
confidence: 99%